The Influence of the Hybrid Working System and Work Discipline on the Work Productivity of Generation Z Employees at PT Solomon Indo Global - Yovie Saputro; Tutik Winarsih (The Eastasouth Management and Business, 2026)
This study aims to analyze the effect of hybrid working systems and work discipline on the work productivity of Generation Z employees at PT Solomon Indo Global. Employing a quantitative explanatory approach, data were collected from 33 Gen Z employees using structured questionnaires and analyzed through multiple linear regression. The results reveal that the hybrid working system has a positive and significant effect on employee productivity (t = 2.358; p = 0.025), reflected in improved work flexibility, effective use of digital technology, and output-based performance management. Work discipline shows a positive but partially non-significant effect on productivity (t = 1.546; p = 0.132), though it contributes positively within the regression model. Simultaneous testing indicates that both hybrid working and work discipline jointly and significantly influence employee productivity (F = 18.324; p < 0.001). The coefficient of determination (R²) of 0.550 indicates that 55% of the variation in employee productivity is explained by the two variables. These findings suggest that the effectiveness of hybrid working for Generation Z employees relies more on system flexibility and technological support, while work discipline serves as a supporting factor. The managerial implication is that organizations need to design adaptive work systems accompanied by clear performance standards and outcome-based monitoring mechanisms to ensure sustainable productivity.